An injectable and biodegradable hydrogel incorporated with photoregulated NO generators to heal MRSA-infected wounds. (1st July 2022) - Lv, Xinyi; Xu, Yan; Ruan, Xiaohong; Yang, Dongliang; Shao, Jinjun; Hu, Yanling; Wang, Wenjun; Cai, Yu; Tu, Yuexing; Dong, Xiaochen
Abstract: The development of degradable hydrogel fillers with high antibacterial activity and wound-healing property is urgently needed for the treatment of infected wounds. Herein, an injectable, degradable, photoactivated antibacterial hydrogel (MPDA-BNN6@Gel) was developed by incorporating BNN6-loaded mesoporous polydopamine nanoparticles (MPDA-BNN6 NPs) into a fibrin-based hydrogel. After administration, MPDA-BNN6@Gel created local hyperthermia and released large quantities of NO gas to treat methicillin-resistant Staphylococcus aureus infection under the stimulation of an 808 nm laser. Experiments confirmed that the bacteria were eradicated through irreversible damage to the cell membrane, genetic metabolism, and material energy. Furthermore, in the absence of laser irradition, the fibrin and small amount of NO that originated from MPDA-BNN6@Gel promoted wound healing in vivo . This work indicates that MPDA-BNN6@Gel is a promising alternative for the treatment of infected wounds and provides a facile tactic to design a photoregulated bactericidal hydrogel for accelerating infected wound healing. Statement of Significance: The development of a degradable hydrogel with high antibacterial activity and wound-healing property is an urgent need for the treatment of infected wounds. Herein, an injectable, degradable, and photo-activated antibacterial hydrogel (MPDA-BNN6@Gel) has been developed by incorporating BNN6-loaded mesoporous polydopamine nanoparticles (MPDA-BNN6 NPs) into a fibrin-based hydrogel. After administration of MPDA-BNN6@Gel, the MPDA-BNN6@Gel could generate local hyperthermia and release large quantities of NO gas to treat the methicillin-resistant Staphylococcus aureus infection under the irradiation of 808 nm laser. Furthermore, in the absence of a laser, the fibrin and a small amount of NO originating from MPDA-BNN6@Gel could promote wound healing in vivo . Graphical abstract: Image, graphical abstract